Biomarkers used in the diagnosis of type 2 Diabetes mellitus: A systematic review (Research, Society and Development, 2025)
Type 2 Diabetes Mellitus (DM2) is a chronic metabolic disease with increasing global prevalence, characterized by insulin resistance and pancreatic cell dysfunction. Early diagnosis and adequate monitoring are essential to prevent micro- and macrovascular complications. This systematic review aimed to synthesize recent scientific evidence on biomarkers used in the diagnosis, prognosis, and follow-up of DM2. Articles published between 2011 and 2025, in Portuguese and English, indexed in databases such as PubMed, SciELO, and American Diabetes Association (ADA) guidelines were included. The results highlight the importance of classic biomarkers, such as fasting blood glucose, glycated hemoglobin (HbA1c), and lipid profile, which remain fundamental in clinical practice due to their accessibility and correlation with glycemic control and cardiovascular risk.  Additionally, inflammatory (IL-6, TNF-α, CRP), hormonal (C-peptide, leptin, adiponectin), genetic (TCF7L2, SLC30A8), and immunological (anti-GAD autoantibodies) biomarkers have demonstrated complementary value in risk stratification, identification of specific phenotypes (such as LADA), and therapeutic personalization. It is concluded that the integration of multiple classes of biomarkers allows for a more precise and individualized approach in the management of type 2 diabetes mellitus (DM2), reinforcing the trend towards precision medicine.